Attenuation of lipopolysaccharide-induced acute lung injury after (pro)renin receptor blockade. (1st May 2015) - Ishii, Kenjiro; Takeuchi, Hiroya; Fukunaga, Koichi; Hirano, Yuki; Suda, Koichi; Hagiwara, Tomoko; Miyasho, Taku; Yamada, Shingo; Nakamura, Rieko; Takahashi, Tsunehiro; Wada, Norihito; Kawakubo, Hirofumi; et al.
ABSTRACT Purpose/Aim: We performed a randomized, prospective animal study to investigate whether inhibiting the renin-angiotensin system with a (pro)renin receptor blocker (PRRB) prevents acute lung injury (ALI) in a rodent model. Materials: We used Thirty-six male Sprague-Dawley rats. We administered lipopolysaccharide (LPS; 2 mg/kg) intratracheally with or without PRRB pretreatment (1 mg/kg/d). Methods: We performed bronchoalveolar lavage (BAL) and lung removal at 4 h after LPS administration and measured levels of inflammatory cytokines, high mobility group box 1 (HMGB-1) protein, and total protein in bronchoalveolar lavage fluid (BALF). Myeloperoxidase (MPO) activity was detected in lung tissue homogenates using a sensitive ELISA. We performed hematoxylin and eosin staining and immunohistochemical staining for nonproteolytically activated prorenin in the left lung. Results: The PRRB decreased leukocyte counts and total protein, tumor necrosis factor (TNF)-α, interleukin (IL)-1β, IL-2, IL-6, and IL-10 levels in the BALF and MPO activity in lung tissue. The PRRB reduced interstitial edema, hemorrhage, and the neutrophil count in the lung tissues. Consistent with the reduction in lung tissue damage, immunohistochemical staining showed that the PRRB decreased the amount of nonproteolytically activated prorenin. Conclusions: The PRRB blocked LPS-induced inflammatory response in the lung and protected against ALI. Therefore, it is a potential therapeutic agent for preventing ALI.